2020
DOI: 10.1111/mcn.13074
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with concurrent wasting and stunting among children 6–59 months in Karamoja, Uganda

Abstract: Children with concurrent wasting and stunting (WaSt) and children with severe wasting have a similar risk of death. Existing evidence shows that wasting and stunting share similar causal pathways, but evidence on correlates of WaSt remains limited. Research on correlates of WaSt is needed to inform prevention strategies. We investigated the factors associated with WaSt in children 6–59 months in Karamoja Region, Uganda. We examined data for 33,054 children aged 6–59 months using June 2015 to July 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
48
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 47 publications
18
48
1
Order By: Relevance
“…Boys had higher odds of wasting, stunting, underweight and WaSt compared with girls in this study (p < 0.05). This is consistent with other similar studies for stunting (Blankenship et al, 2020;De Vita et al, 2019;Fenta et al, 2020;Geda et al, 2021;Wali et al, 2020) Geda et al, 2021) and WaSt (Garenne et al, 2019;Odei Obeng-Amoako, et al, 2021). Little is known about gender effects on all forms of malnutrition.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Boys had higher odds of wasting, stunting, underweight and WaSt compared with girls in this study (p < 0.05). This is consistent with other similar studies for stunting (Blankenship et al, 2020;De Vita et al, 2019;Fenta et al, 2020;Geda et al, 2021;Wali et al, 2020) Geda et al, 2021) and WaSt (Garenne et al, 2019;Odei Obeng-Amoako, et al, 2021). Little is known about gender effects on all forms of malnutrition.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with a study in Senegal and a meta-analysis of 84 countries that found that WaSt declined after 24 months of age (Garenne et al, 2019;Khara et al, 2018). A Ugandan study reported this decline after 36 months (Odei Obeng-Amoako, et al, 2021). These findings suggest that children aged less than 24 months (maybe up to 36 months) need special attention from families, programmers and the Ministry of Health.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Acute malnutrition also known as wasting is characterized by a rapid deterioration in nutritional status over a short period that causes a child to become too thin for his or her height because of weight loss or failure to gain weight [3][4][5]. For children, it can be measured using the weight-for-height nutritional index or mid-upper arm circumference [6,7]. It is de ned as moderate acute malnutrition (MAM) and severe acute malnutrition (SAM) whereas; MAM: is WHZ≥ -3Z score &<-2Z score or MUAC ≥ 115 mm & < 125 mm (≥ 11.5 cm & < 12.5 cm) and SAM: is de ned by visible severe wasting, or by the presence of bilateral pitting edema of nutritional origin, or WHZ< -3Z score or MUAC < 115 mm (< 11.5 cm) in children aged 6-59 months [2].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors contribute to childhood wasting. The common determinants reported by several studies include gender, age of the child [7,[22][23][24], monthly income [22,24], diarrhea in the previous two weeks [25][26][27], not consuming additional food during pregnancy/lactation [28,29], non-exclusive breastfeeding practices [26,30], larger family size [26], mothers education [22,26], presence of ARI [26,31], attending ANC [7,29,32], immunization status [33,34], mother not having consumed extra food during this pregnancy/lactation [4,22].…”
Section: Introductionmentioning
confidence: 99%